Validasi Metode Analisis Benzena Secara Kromatografi Cair Kinerja Tinggi dan Aplikasinya untuk Analisis Pembentukkan Benzena yang dihambat oleh Glukosa dan Fruktosa dalam Minuman ringan - , ETTY SULISTYOWATI, Prof. Dr. Sudibyo Martono, M.S., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Benzoate and ascorbic acid in soft drinks can trigger the formation of benzene. The formation of benzene in soft drinks can be prevented with the use of glucose and fructose so it is needed to know which materials are most effective in inhibiting the formation of benzene. The study was conducted to find a method of analysis of benzene in soft drinks that validated analytical results obtained so precise and accurate. Methods development for the analysis of benzene is High Performance Liquid Chromatography (HPLC) using a mobile phase of acetonitrile : aquabides (60: 40 v/v) with flow rate 0.8 mL / min, the column used LiChrosob Phenomenex RP-18, the injection volume 20 Î¼L, and UV-Vis detector at Î»max 205. 1250 mg/L of sodium benzoat and 1000 mg/L of ascorbic acid can produce benzena in the simulation solution that can be inhibited by glucose and fructose.The results of the analytical methods are developed to find the validation requirements, which include accuracy, precision, selectivity, linearity, limit of detection and limit of quantitation for analyzing benzene in soft drinks. The results of simulation analysis of benzene in soft drinks solution, statistical tests showed difference in the inhibition of the formation of benzene significant by glucose and fructose, were added to the concentration in soft drinks that is added to the glucose concentration of 0.10